CALCULATION OF TEMPERATURE CHANGES IN THE GREENHOUSE SOIL LAYER USING GEOTHERMAL ENERGY (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article presents the results of calculating the change in temperature in the soil layers of a greenhouse, in which a temperate climate is created using solar and geothermal energy.  It is shown that the distribution, absorption and accumulation of heat in the soil layers depend on the incoming solar energy, the composition of the soil layer, humidity and on the inclination or smoothness of the soil surface.